2008
DOI: 10.1002/bies.20734
|View full text |Cite
|
Sign up to set email alerts
|

The role of ATF‐2 in oncogenesis

Abstract: Activating Transcription Factor-2 is a sequence-specific DNA-binding protein that belongs to the bZIP family of proteins and plays diverse roles in the mammalian cells. In response to stress stimuli, it activates a variety of gene targets including cyclin A, cyclin D and c-jun, which are involved in oncogenesis in various tissue types. ATF-2 expression has been correlated with maintenance of a cancer cell phenotype. However, other studies demonstrate an antiproliferative or apoptotic role for ATF-2. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
87
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 100 publications
(84 reference statements)
3
87
0
1
Order By: Relevance
“…We also showed that NFATc, ATF2, and c-Jun induce Angptl2 expression, providing a mechanism for tumor cell ANGPTL2 induction. These findings are consistent with previous reports showing that activation of ATF/CREB family proteins and/or the calcineurin/NFATc pathway occurs in aggressively advanced tumors (6,19,28,29). We have reported that obese adipose tissue-related endoplasmic reticulum (ER) stress increases ANGPTL2 secretion or expression in adipocytes (13).…”
Section: Discussionsupporting
confidence: 93%
“…We also showed that NFATc, ATF2, and c-Jun induce Angptl2 expression, providing a mechanism for tumor cell ANGPTL2 induction. These findings are consistent with previous reports showing that activation of ATF/CREB family proteins and/or the calcineurin/NFATc pathway occurs in aggressively advanced tumors (6,19,28,29). We have reported that obese adipose tissue-related endoplasmic reticulum (ER) stress increases ANGPTL2 secretion or expression in adipocytes (13).…”
Section: Discussionsupporting
confidence: 93%
“…This interaction is finely tuned by several stimuli and it is responsible for different cellular response ranging from apoptosis to proliferation. 7,9,36 One of the crucial partners of this dimeric complex is the proto-oncogene cJUN. The JNK/c-Jun/ ATF2 pathway regulates a plethora of target genes containing AP1-binding sites, including those that controlling survival and apoptosis, metalloproteinases and nuclear hormone receptors.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Independent of its transcriptional activity, ATF2 also plays an important role in the DNA damage response and in the regulation of intra-S-phase checkpoint (reviewed in Ref. 7). Several studies reported a correlation between ATF2/JNK-mediated activation and resistance to DNA damaging agents.…”
mentioning
confidence: 99%
“…In addition, mitogen-activated protein kinase 14 (p38) mitogen-activated protein kinase (MAPK) was activated by AOH in NIH3T3 cells (12). Activating transcription factor 2 (ATF2) is one of the downstream molecules of the MAPK signal pathway and can be activated by p38MAPK and mitogen-activated protein kinase 8 (JNK) (13,14). ATF2 is a member of ATF or cAMP-responsive element binding protein (CREB) family, which contains the basic/leucine zipper motifs (bZIP) and can bind to cAMP-responsive elements (CREs) (15,16).…”
Section: Introductionmentioning
confidence: 99%